China’s environmental “fee-to-tax” and foreign direct investment—An empirical study based on intensity difference-in-differences - Huang, Jiqiang; Li, Yanfeng (Frontiers in Environmental Science, 2023)
To protect and improve the environment, reduce pollutant emissions, and promote ecological civilization, China implemented “the Environmental Protection Law of the People’s Republic of China” on 1 January 2018. However, what is the impact of strict environmental regulation on foreign direct investment (FDI)? The study uses the data from 287 cities in 30 of China’s provinces between 2003 and 2019 and constructs an intensity difference-in-difference model to test the impact of China’s environmental “fee-to-tax” on FDI. Empirical results show that environmental “fee-to-tax” significantly boosts FDI. The “pollution halo” hypothesis is confirmed, and the findings hold up through robustness tests. In addition, the heterogeneity test found that environmental “fee-to-tax” mainly promoted FDI in the eastern and central regions but not significantly in the western regions. Further expansion found that environmental “fee-to-tax” can effectively reduce the emission of pollutants. The results provide important policy implications for deepening the environmental protection tax reform and optimizing FDI.